Evaluation of interdisciplinary treatment outcomes in patients with cleft lip and palate. Part 1. - Racka-Pilszak, Bogna; Wojtaszek-Słomińska, Anna; Zdun-Ryżewska, Agata; Majkowicz, Mikołaj; Banaszkiewicz, Agnieszka; Basiński, Krzysztof (Forum Ortodontyczne / Orthodontic Forum, 2018)
Cleft palate is the most common congenital defect within the facial skeleton. Coexisting facial deformations are not only visible, but also audible after surgery – children born with cleft lip and palate belong to the risk group for occurrence of speech-language disorders. Due to this fact, they may face inappropriate responses of people around, which may cause poor mental condition. Majority of subjects (ca. 67 percent) experienced unpleasant feelings caused by people around them and noticed contribution of the cleft to lowered selfconfidence. Almost 56 percent of the studied group notices influence of this congenital defect on ability to establish social relationships, and 33 percent – on results achieved at school. Aim. The main aim of the study was to evaluate efficacy of treatment in patients with cleft lip and palate as well as usefulness of applied research tools (questionnaire, GOSLON score). Material and methods. Study material included a group of 45 subjects with unilateral and bilateral cleft lip and palate, who completed multidisciplinary treatment. Mean age of the subjects was 22 years. The study was conducted at the Outpatient Orthodontic Clinic of the University Dentistry Centre of the Medical University of Gdansk. Research methods included evaluation of the occlusal abnormalities before and after treatment using GOSLON score, questionnaire completed by the patient, and specialist speech-language examination. Results. The highest percentage of satisfied patients was observed among subjects, who underwent orthodontic treatment (ca. 90 percent), which corresponded with established improvement in occlusal conditions after treatment. Appearance of the respective facial areas was mainly defined as good or very good. It was also noticed that the more the patient was satisfied with speech-language therapy, the more he/she was satisfied with speech quality. Conclusions. Evaluation of final outcomes of the multidisciplinary treatment in patients with cleft lip and palate constitutes high clinical significance in order to make further development and to evaluate currently used therapeutic management standards. (Racka-Pilszak B, Wojtaszek-Słomińska A, Zdun-Ryżewska A, Majkowicz M, Banaszkiewicz A, Basiński K. Evaluation of interdisciplinary treatment outcomes in patients with cleft lip and palate. Part 1. Orthod Forum 2018; 14: 270- 83).